Three dimensional modelling of mutant Kir2.1 channel PIP2 interactions help stratify arrhythmia severity in Andersen Tawil syndrome type 1. (3rd October 2022) - Gutierrez-Espinosa De Los Monteros, L; Martinez, F; Cruz, F M; Moreno-Manuel, A I; Sanchez, P; Vera-Pedrosa, M L; Martinez-Carrascoso, I; Bermudez-Jimenez, F; Macias, A; Jalife, J
Abstract: Background: Andersen-Tawil type 1 (ATS1) is associated with loss-of-function mutations in the inward rectifier potassium channel Kir2.1, which controls cardiac excitability and impulse conduction. Phosphatidylinositol-4, 5-bisphosphate (PIP2) acts as an essential cofactor regulating the opening of Kir2.1 channels. Fifty percent of reported ATS1 mutations affect Kir2.1-PIP2 interactions, leading to ECG defects, ventricular arrhythmias and sudden cardiac death (SCD) by mechanisms that are poorly understood. Purpose: To test the hypothesis that the degree of arrhythmogenic severity of ATS1 mutations disrupting PIP2-Kir2.1 binding may be predicted by the level of polarization of the mutant Kir2.1 channel pore. Methods: We first used a statistical mean value approach to classify the 40 known arrhythmogenic ATS1 mutations impacting Kir2.1-PIP2 interaction (N=260 individuals) according to arrhythmogenic severity, ranging from SCD through ventricular bigeminy and QT prolongation. We then generated 3D in-silico atomic models of the wildtype channel and the 10 mutant channels with the most severe arrhythmic phenotype to assess the mechanism of the structural defects associated with Kir2.1-PIP2 disruption. Results: Our cardiac lethality scoring stratifying Kir2.1 mutations according to arrhythmogenic severity was validated by three additional biostatical quantitative measures. On in-silico modelling, wildtype Kir2.1 channels without PIP2 binding had transmembrane and cytoplasmic pore radius of 1.5 and 3 Å, respectively. Kir2.1-PIP2 interactions increased transmembrane and cytoplasmic pore radius to 3 and 6 Å, respectively. All 10 Kir2.1 mutations had similar transmembrane and cytoplasmic pore radius of ∼1.0 and ∼3.0 Å, respectively. The most severe mutations yielded pore channels with highly polarized electrostatic forces. Remarkably, simulations showed a descending electrostatic pattern at the transmembrane region of PIP2 binding, where the more severe the mutation, the more positive that region was. Structural changes produced by mutations correlated with cardiac severity (R2=0.51; p<0.005) in that the most drastically altered protein structure correlated with the most severe arrhythmic phenotype. Conclusions: Computer simulations of mutant Kir2.1 channel structure from the most arrhythmogenic to the least arrhythmogenic predict a gradual decrease in polarization of electrostatic forces along the Kir2.1 channel pore. The results reveal a novel mechanistic stratification of arrhythmogenic severity of ATS1 mutant Kir2.1 channel-PIP2 interactions and open new pathways for developing more personalized ATS1 patient therapies. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): La Caixa Banking Foundation under the project code HR18-00304Fundaciόn La Marato TV3: Ayudas a la investigaciόn en enfermedades raras 2020